2002
DOI: 10.2343/geochemj.36.235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photooxidation on .DELTA.13C of benzo(a)pyrene and benzo(e)pyrene in the atmosphere.

Abstract: The objective of this study is to clarify the effect of photooxidation on δ 13 C of benzo(a)pyrene (BaP) and benzo(e)pyrene (BeP) in the atmosphere. They are structural isomers but are known to differ significantly in terms of photooxidation rate. The results of literature reviews and measurements revealed that the concentration ratio of BaP and BeP (BaP/BeP) is almost constant independent of the fuel type and emission source (almost constant at 2.1), while δ 13 C values for the two PAHs are almost equal. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 36 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Tanaka and Sakata (2002) summarized previous laboratory results of the BaP/BeP ratios from various fuels (gasoline, light oil, heavy oil, coal, and wood). They concluded that the BaP/BeP ratio is almost a Original data given in units of nmol m -3 were converted by assuming a molecular weight to be 250 g mol −1 .…”
Section: Spatial Distributions Of Pah Level In Asian Pacific Regionmentioning
confidence: 99%
“…Tanaka and Sakata (2002) summarized previous laboratory results of the BaP/BeP ratios from various fuels (gasoline, light oil, heavy oil, coal, and wood). They concluded that the BaP/BeP ratio is almost a Original data given in units of nmol m -3 were converted by assuming a molecular weight to be 250 g mol −1 .…”
Section: Spatial Distributions Of Pah Level In Asian Pacific Regionmentioning
confidence: 99%
“…In Japan, it has been reported that various substances, including non-sea-salt sulfate (nss-SO 4 2-), heavy metals and organic compounds, are transported from the Asian continent to Japan during winter and spring when the airflows from the Asian continent are dominant (Mukai et al, 1990(Mukai et al, , 1994Ichikawa et al, 1998;Tanaka and Sakata, 2002;Sakata and Marumoto, 2005;Sakata et al, 2006). Moreover, Tanimoto et al (2005) showed that the spring maximum of surface O 3 over Japan is significantly caused by NO x from sources in China and Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Tracers of emissions from coal burning are useful for such evaluation. Several tracers have been used for precipitation and aerosol samples, namely, sulfur isotopes in nss-SO 4 2- (Kitamura et al, 1993), lead isotopes (Mukai et al, 1994), carbon isotopes in some polycyclic aromatic hydrocarbons (Tanaka and Sakata, 2002), selenium composition (Se(IV) and Se(VI)) (Kagawa et al, 2003), and concentration ratio of Pb/Zn…”
Section: Hgmentioning
confidence: 99%
“…Thus, the long-range transport of air pollutants from China has a measurable impact on atmospheric composition in Japan, which is located at the forefront of the eastern regions of the Asian continent. Studies over the past few decades have shown that various gaseous and particulate pollutants, including non-sea-salt sulfate (nss SO 4 2 − ), nitrate, O 3 , heavy metals, PAHs, and black carbon, are transported from the Asian continent to Japan in winter and spring when the airflows from the Asian continent are dominant (Mukai et al, 1990(Mukai et al, , 1994Ichikawa et al, 1998;Tanaka and Sakata, 2002;Matsumoto et al, 2003;Uno et al, 2003;Tanimoto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%